Design and Development of a Segmented Rubbe-tracked Vehicle for Sepang Peat Terrain in Malaysia - Rahman, Md. Ataur (2005)
The study describes the design and development of a segmented rubber tracked vehicle for operating on unprepared peat terrain. The vehicle was to traverse accurately and reliably on the 18.79k~lmlo~w bearing capacity peat terrain. The study observed four main contributions towards determining the mechanical properties of peat terrain, developing simulation models for optimizing the design parameters of the vehicle, designing and developing the vehicle to be able to traverse accurately on low bearing capacity peat terrain, and designing an innovative instrumentation system on the vehicle for collecting relevant data to measure vehicle tractive performance. An analytical framework for determining the mechanical properties of peat soil in view of predicting the tractive performance of tracked vehicle was presented. It took into account the load-sinkage and shearing characteristics of peat. An experimental study on the mechanical properties of peat was conducted in Sepang, Selangor, Malaysia. The stiffness values of surface mat and underlying weak peat deposit from load-sinkage test were determined by specially made bearing capacity apparatus. The mean values of surface mat stiffness before and after drainage were found to be 31kN/m3 and 46k~lr-n~~ respectively. The mean value of underlying peat stiffness before and after drainage were found to be 252kN/m3 and 380kN/m3, respectively. The mean value of internal frictional angle, cohesiveness and shear deformation modulus of the peat soil sample were determined using a direct shear box apparatus in the laboratory. The mean value of internal frictional angle, cohesiveness and shear deformation modulus of the peat soil before and after drainage were found to be 22.80" and 24.3 lo, 2.63kN/m2 and 2.89kN/m2, and 1.2 1 cm and 1.37cm7 respectively. A new simulation technique for studying the basic design parameters of the vehicle with rigid link tracks system on Sepang peat terrain in Malaysia was also presented. The proper track width, ground contact length, pitch and grouser height, idler diameter and location, sprocket diameter and location, road-wheel diameter and geometrical arrangement, the ratio of the road-wheel spacing to track pitch, location of the center ofgravity (CG) of the vehicle are important to select to ensure good tractive performance of the vehicle on unprepared peat terrain. Simulation technique was then used to optimize the design parameters of the vehicle by establishing mathematical models for the trackterrain interaction mechanism. In the simulation study, the 25.5kN vehicle including payloads of 5.89kN was considered to traverse on the peat terrain at lOkm/h. The simulation study for the vehicle of straight running motion showed that the nominal ground pressure of the vehicle was 23.3% lower than the bearing capacity of the peat terrain. From simulated tractive performance results, vehicle average motion resistance coefficient of 6.8 to 7.9%, drawbar pull coefficient of 25.22 to 47%, and tractive efficiency of 74 to 77%, were found for the slippage of 5 to 20%. For the simulation study on the vehicle of turning motion, the result showed that the vehicle ground contact pressure exit from outer track was 14.61% and from the inner track was 6.67% lower than the bearing capacity of the Sepang peat terrain, the sinkage of the vehicle outer track 10.5% lower and inner track 22.5% lower, torque of the outer track sprocket 7.85% higher than the turning moment resistance of the vehicle, and lateral resistance 7.4% higher than the centrifugal force of the vehicle which was ensured the vehicle to maintain the steady state turn on the Sepang peat terrain at a turning speed of 1 Okm/h. The vehicle field tests were conducted on three different types of peat terrains: Terrain Type I, Terrain Type 11, and Terrain Type I11 with two loading conditions at travel speeds of 6km.h and 10km.h. The results showed that the tractive effort of the vehicle was increased 13.7 1 % for Terrain Type 1, 1 1 .O9% for Terrain Type 11, and 13.53% for Terrain Type I11 when the traveling speed was increased from 6kmh to 10krnIh. From the variation of the vehicle tractive operating environment, it was found that the tractive effort of the vehicle at traveling speed of 6kmih increased 8.08%, 5.12%, and 14.14% for changing the vehicle operating environment from Terrain Type I to Terrain Type 11, Terrain Type I1 to Terrain Twe 111, and Terrain Type I to Terrain Type 111, respectively. Similarly, the tractive effort for the vehicle at a traveling speed of lOkm/h increased 6.32%, 7.42%, and 14.22% for changing the vehicle operating environment from Terrain Type I to Terrain Type 11, Terrain Type I1 to Terrain Type 111, and Terrain Type I to Terrain Type 111, respectively. Furthermore, the tractive effort of the vehicle at a traveling speed of 6kmh increased 2.28% for Terrain Type I, 5.124% for Terrain Type 11, and 6.46% for Terrain Type 111 when the vehicle changing operating loading condition from without payload to with full payload. Similarly, the tractive effort of the vehicle at a traveling speed of 1Okm/h increased 1.76% for Terrain Type I, 2.61% for Terrain Type 11, and 6.69% for Terrain Type I11 when the vehicle changing operating loading condition from without payload to with full payload.